Attributes of Quality of Accommodation Facilities and Room Capacity Utilization of 3-5 Star Hotels in Nairobi, Kenya - N. M., Miricho; A., Adedipe (International Journal of Scientific Research and Management (IJSRM), 2018)
There are specific quality requirements usually established in accordance with standards at either government or private levels for hotel accommodation facilities. One of these basic requirements is high quality of accommodation facilities which supposed to anchor room capacity utilisation of 3-5 star hotels in Nairobi, Kenya. The attributes of quality of accommodation facilities comprised of room flooring, decorations, bed and beddings, lightings and heating, comfort of bedroom, cleanliness, comfort of bathroom, towels, furniture and furnishings, toiletries and amenities, space and ventilation of the rooms. However, hotels with more accommodation quality attributes are likely to attract higher and better room capacity utilisation. Therefore, the study sought to examine the relationship between quality of accommodation facilities and room capacity utilisation of 3-5 star hotels in Nairobi, Kenya. The study hypothesized that there is no significant relationship between quality of accommodation facilities and room capacity utilisation of 3-5 star hotels in Nairobi, Kenya. The target population involved all the 3-5 star hotels in Nairobi, Kenya. A census of hotel general manager and front office managers consisting of 60 respondents was conducted through stratification of all the hotels. Questionnaire was used as instruments for data collection with 95.1% response rate and the data collected were analyzed using descriptive statistics to determine variable characteristics while Pearson correlation was used to establish the pattern of relationship and association of the variables. Also, linear regression analysis was involved to determine the level of significant and test hypothesis. The Pearson correlation result (r=-0.542, p=0.000) indicated that quality of accommodation facilities had a strong positive relationship and association with room capacity utilisation. The regression analysis coefficient R=0.792 and adjusted squared coefficient R2=0.527 were recorded which implied that the study variables explained 52.7% of the variations of room capacity utilisation. The regression model revealed comfort of bedroom, comfort of bathroom, bed/beddings and cleanliness as the four attributes of quality of accommodation facilities that were significant variable predictors of room capacity utilisation. The null hypothesis was rejected as there is significant relationship between quality of accommodation facilities and room capacity utilisation. The study concluded that an improvement in quality of accommodation facilities will cause positive significant changes in room capacity utilisation. The study recommends improvement on comfort of bedroom, comfort of bathroom, bed and beddings as well as general cleanliness for better room capacity utilisation of 3-5 star hotels in Nairobi, Kenya